Safety and efficacy of biologic immunosuppressive treatment in juvenile idiopathic arthritis associated with inborn errors of immunity - Accardo, V.; Pagnini, I.; Maccora, I.; Marrani, E.; Mastrolia, M. V.; Simonini, G. (Frontiers in Pediatrics, 2024)
To describe clinical features, therapeutic outcomes and safety profile in patients affected by Juvenile Idiopathic Arthritis (JIA) and Inborn Errors of Immunity (IEI) treated with biological DMARDs. METHODS We have enrolled three patients, followed in Pediatric Rheumatology Unit at Meyer Children's Hospital in Florence, affected by JIA, according to ILAR criteria, and IEI according the IUIS Phenotypical classification for Human Inborn Errors of Immunity : two patients had 22q11.2 deletion syndrome (22q11.2DS) and one patient had Xlinked-agammaglobulinemia (XLA).RESULTS Case 1: 6 years and 2 months old male affected by 22q11.2DS, associated to oligoarticular-JIA since he was 2 years old. He was treated with NSAID and methotrexate, oral glucocorticoid without benefit. Treatment with Etanercept allowed him to achieve remission after 10 months. Case 2: 6 years and 2 months old female affected by 22q11.2DS, with oligoarticular-JIA since she was 3 years and 11 months old. She was treated with NSAID, joint injection and methotrexate, without clinical response. Treatment with Adalimumab, allowed to achieve the remission after 6 months. Case 3: 12 years and 2 months old male affected by XLA, associated to polyarticular-JIA since he was 9 years and 11 months old. He was treated with NSAID, methotrexate, joint injections and oral glucocorticoid with no benefits. He failed to respond to anti-TNF-alpha, Tocilizumab and Abatacept. Currently he is undergoing therapy with Sirolimus plus Abatacept, which allowed him to achieve remission after 4 months.